ChSch9 is required for infection-related morphogenesis and pathogenicity in Colletotrichum higginsianum. Issue 6 (2nd November 2021) - Sohail, Muhammad Aamir; Yuan, Qinfeng; Yan, Yaqin; Huang, Junbin; Hsiang, Tom; Zheng, Lu
Abstract: Colletotrichum higginsianum is an economically important anthracnose pathogen of crucifers that causes losses worldwide. For comprehensive control of anthracnose disease, it is essential to understand the mechanisms of pathogenicity in C. higginsianum . The Ser/Thr kinase Sch9 belonging to the AGC (protein kinase A, G, and C) kinase family, commonly found in eukaryotes, plays a vital role in various cell signalling pathways and development. However, it has not been studied in Colletotrichum species. Three domains, Protein kinase C conserved region 2 (C2), Serine/Threonine protein kinase catalytic (S_TKc) and Extension to Ser/Thr-type protein kinases (S_TK_X), were identified in the C. higginsianum Sch9 (ChSch9) protein. Phylogenetic analysis indicated that ChSch9 is closely related to the AGC kinase family, which is conserved in fungi. Deletion of ChSch9 caused defects in hyphal morphology, growth and conidiation. In addition, deletion of ChSch9 was associated with reduced tolerance to hyperosmotic, cell wall and oxidative stresses in C. higginsianum, and ChSch9 deletion mutants were more tolerant to heat. Furthermore, we found that ChSch9 might be involved in the pyruvate–acetaldehyde fermentation pathway. Importantly, deletion of ChSch9 led to a reduction in appressoria and infective hyphae formation, resulting in defects in virulence. Collectively, the results of this study indicate that ChSch9 is required for infection-related morphogenesis and virulence in C. higginsianum .